Antecedents of corporate sustainability in a multicultural society and the globalized economy - Zarkada, Anna K.; Tzoumaka, Eugenia; Niros, Meletios I. (My University, 2018)
The sustainability of a corporation requires the support of not only its customers, but also its multiple stakeholders. To survive and thrive, it needs performative and social legitimacy, that is, to be respected as a local community member (so as to be allowed to operate without hindrances) and to be perceived as an acceptable provider of goods and services,a desirable employer and a lucrative investment opportunity (so as to be able to draw the necessary resources). In a nutshell, it needs a strong and positive corporate brand image that inspires confidence in people and a desire to form stakeholder relationships with it. In the globalized economy of the 21st century, however, corporate brand image, and the resulting public support, are subject to national identity congruence. Countries become increasingly more multicultural, national identities and perceptions of ‘foreignness’ are renegotiated, country stereotypes change, and the balance of ethnocentrism and cosmopolitanism in a society shifts in ways that affect public support for corporations. Governments might strive to attract Foreign Direct Investment (FDI) and promote exports to drive economic growth, but, at the corporate level, policies and incentives can be outweighed by public resistance (in forms such as consumer boycotts or protests) by a host-country public which might perceive multinational corporations as threats to local businesses. We here argue that it is individual decision-makers that can make the investment climate hostile and drive investors away despite government efforts to attract and nurture them. This paper presents an integrative conceptual model of individual decision-making process regarding the formation of stakeholder relationship with a corporation which can predict public support for a corporation in the current globalized and recessionary economy of a multicultural society. Our review of the current state in the scientific fields of FDI theory, stakeholder theory, social psychology, international management and marketing, individual decision-making/consumer behavior, behavioral economics, and corporate branding and corporate reputation theory, revealed that even though individual constructs are extensively investigated, integrative models are, at best, scarce (Balmer&Greyser, 2006; Kaynak&Herbig, 2014; Makanyeza, 2015; Xie, Batra, & Peng, 2015) thus making it impossible to forecast public support for a corporation. Moreover, hardly any empirical work has been carried out in the context of Greece (Anastasiadou, 2014) and none under the extreme circumstances of an economic downturn, to which FDI is seen as an antidote, and a fast-changing demography, which is triggering ethnocentrism and makes corporate brand image and support for a firm more contextual than ever before.
Keywords: Corporate Brand Image; Country of origin effects; Ethnocentrism; FDI; Public Support; Patriotism; stakeholder theory